Anti-inflammation furanoditerpenoids from Caesalpinia minax Hance. (September 2015) - Dong, Ruijuan; Yuan, Jiuzhi; Wu, Shilong; Huang, Jian; Xu, Xiaotong; Wu, Zhaohua; Gao, Huiyuan
Abstract : Graphical abstract: Twelve furanocassane derivatives, including six previously unreported were isolated from the seeds of Caesalpinia minax Hance. Neocaesalminin A (1 ) was found with an unusual A- seco -rearranged cassane skeleton. The inhibitory effect on NO production for all compounds was evaluated in vitro. Furanoditerpenes were responsible for this herb's anti-inflammation activity. Highlights: Cassane furanoditerpenes, six previously unreported were isolated from seeds of Caesalpinia minax Hance. Neocaesalminin A, a furanoditerpene, has an unusual A- seco -rearranged cassane skeleton. Inhibitory effects on NO production for all compounds were evaluated in vitro. Cassane furanoditerpenes were responsible for the Caesalpinia minax Hance anti-inflammation activity. Abstract: Cassane skeletons are rare in nature, but often possess valuable medicinal properties. A furanoditerpenoid with an unusual A- seco -rearranged cassane skeleton, neocaesalminin A, and five furanoditerpenoids were isolated from seeds of Caesalpinia minax Hance, along with six known cassane derivatives, 7- O -acetyl-bonducellpin C, caesalmin F, caesalmin C, ζ-caesalmin, caesalmin E1 and caesalpinin K. Compound structures were determined by spectroscopy (HR-ESI-MS, UV, IR, 1D NMR, 2D NMR), X-ray crystallography and quantum chemical computation of electronic circular dichroism). Three of the previously known compounds exhibited significant inhibition of nitric oxide production of RAW264.7 macrophages stimulated by lipopolysaccharide (LPS).